2020
DOI: 10.1155/2020/7537924
|View full text |Cite
|
Sign up to set email alerts
|

5-2-1 Criteria: A Simple Screening Tool for Identifying Advanced PD Patients Who Need an Optimization of Parkinson’s Treatment

Abstract: Objective. 5-(5 times oral levodopa tablet taken/day) 2-(2 hours of OFF time/day) 1-(1 hour/day of troublesome dyskinesia) criteria have been proposed by a Delphi expert consensus panel for diagnosing advanced Parkinson's disease (PD). e aim of the present study is to compare quality of life (QoL) in PD patients with "5-2-1 positive criteria" vs QoL in PD patients without "5-2-1 positive criteria" (defined as meeting ≥1 of the criteria). Methods. is is a cross-sectional, observational, monocenter study. ree di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 32 publications
2
42
1
1
Order By: Relevance
“…To the best of our knowledge, this study is the first to use the 5-2-1 diagnostic criteria to assess the effect of APD on patient QoL and determine the factors that most affect QoL in a Japanese population. Patient demographic data indicated that patients with APD represented a slightly younger population compared with the non-APD group, which is not consistent with the findings of the previous OBSERVE-PD study or with another study using the 5-2-1 diagnostic criteria in Spain [23]. ese findings are also not in line with the results from a previous systematic review, which showed that older age is predictive of increasing disability [24].…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…To the best of our knowledge, this study is the first to use the 5-2-1 diagnostic criteria to assess the effect of APD on patient QoL and determine the factors that most affect QoL in a Japanese population. Patient demographic data indicated that patients with APD represented a slightly younger population compared with the non-APD group, which is not consistent with the findings of the previous OBSERVE-PD study or with another study using the 5-2-1 diagnostic criteria in Spain [23]. ese findings are also not in line with the results from a previous systematic review, which showed that older age is predictive of increasing disability [24].…”
Section: Discussioncontrasting
confidence: 81%
“…Furthermore, factors that reduce QoL at each stage could be analyzed by categorizing patients into stages using the 5-2-1 criteria, which may be useful for treatment selection based on their condition. e study conducted in Spain also reported that QoL was worse in patients meeting ≥1 of the 5-2-1 criteria and suggested the usefulness of these criteria in identifying patients requiring optimization of PD treatment [23]. While the 5-2-1 criteria could be a helpful tool in identifying patients requiring a change in their clinical regimen, the definition and treatment of APD require further standardization.…”
Section: Discussionmentioning
confidence: 98%
“…[11,15] These attempts have led to the development of a simple screening tool, the so-called 5-2-1 screening criteria, to identify advanced PD patients in whom any AT may be considered. [14,16,17] According to these criteria patients who fulfil at least one of the following characteristics have advanced PD: 5 times oral levodopa tablets taken daily; 2 hours of off time per day; 1 hour of troublesome dyskinesia per day. Although these criteria are easy to use and possibly sensitive in diagnosing advanced PD,[16,17] the 5-2-1 criteria have not been developed nor tested using prospective data from routine care.…”
Section: Introductionmentioning
confidence: 99%
“…[14,16,17] According to these criteria patients who fulfil at least one of the following characteristics have advanced PD: 5 times oral levodopa tablets taken daily; 2 hours of off time per day; 1 hour of troublesome dyskinesia per day. Although these criteria are easy to use and possibly sensitive in diagnosing advanced PD,[16,17] the 5-2-1 criteria have not been developed nor tested using prospective data from routine care. An important limitation is the lack of data on the diagnostic accuracy of the 5-2-1 criteria, including a reliable estimation of the positive predictive value.…”
Section: Introductionmentioning
confidence: 99%
“…In den letzten Jahren wird versucht, die Indikationsstellung sowohl für die THS als auch für die Medikamentenpumpen zu operationalisieren: Patienten, die Levodopa mehr als 5-mal täglich benötigen und trotz optimaler oraler levodopa-und nicht levodopabasierter Therapien schwere, störende Off-Phasen (länger als 1-2 Stunden am Tag) haben, sollten zur fachärztlichen Beurteilung mit der Frage für eine GUT überwiesen werden, auch wenn die Krankheitsdauer kürzer als 4 Jahre ist [5][6][7]. Aufbauend auf diese Empfehlung sind neuerdings die 5-2-1-Kriterien als Screening-Tool formuliert worden [8,9]. Das heißt, wenn ein Patient mehr als 5 Einnahmezeitpunkte von Levodopa pro Tag braucht, Dieses Dokument wurde zum persönlichen Gebrauch heruntergeladen.…”
Section: Indikation Für Gutunclassified